The Impact of Media Advertisement on Consumers Purchasing Behaviour (Patan Pragya, 2020)
Marketers spend a massive amount on various media platforms to influence consumer behavior. Advertisement on every media platform has a different component that involves the Consumer for different purposes. Technological innovation has led to changes in Consumer's media habits. Hence, a deeper understanding of advertisements on various media platforms, and their implications on consumer behavior needs to be established. This study aims to examine the relationship between advertisement dimensions such as printing, broadband, outdoor and social media, and consumer purchasing behavior. Data were collected with the help of a structured questionnaire by email and direct interviews with the consumers located in Kathmandu valley. The findings revealed that the advertisement media dimensions had a strong correlation with consumer purchasing behavior. It also indicated that printing, outdoor and social media were statistically significant, and broadband media were found to be statistically insignificant with consumers 'purchase behavior